Temporal perception in closed-skill sports: An experimental study on expert swimmers and runners - Perrone, S.; Rinaldi, L.; Gatti, D.; Girelli, L. (Psychology of Sport and Exercise, 2023)
The cognitive benefits of closed-skill sports practice have so far been scantily investigated. Here, we thus focused on the potential impact of swimming and running - two sports that highly rely on a precise control of timing - on time processing. To investigate the impact of these closed-skill sports on time perception and estimation, three groups of participants (for a total of eighty-four young adults) took part in the present study: expert swimmers, expert runners, and non-athletes. The ability to process temporal information in the milliseconds and seconds range was assessed through a time reproduction and a finger-tapping tasks, while a motor imagery paradigm was adopted to assess temporal estimation of sport performance in a wider interval range. We also employed the Vividness of Movement Imagery Questionnaire to assess the individual's ability of motor imagery. Results showed that closed-skill sports, specifically time-related disciplines, enhance motor imagery and time perception abilities. Swimmers were more accurate and consistent in perceiving time when compared to runners, probably thanks to the sensory muffled environment that leads these athletes to be more focused on the perception of their internal rhythm.